FAKTOR-FAKTOR YANG MEMPENGARUHI KUALITAS TIDUR PADA MAHASISWA PROGRAM STUDI ILMU KEPERAWATAN UNIVERSITAS RIAU - Muhammad " Akram; Safri " "; Rismadefi " Woferst (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2016)
Abstract Individuals are required to comply basic human needs in order to survive, one of the basic human needs is sleep. Having good quality sleep is very important for everyone. Quality of sleep is a condition where an individual's sleep make freshness and fitness when wake up. In young adults often have sleep disturbances and changes in sleep hours. The aims of this study was to determine the factors that affect the quality of sleep in college students used descriptive correlation research design with cross sectional approach. The sampling method using stratified random sampling with 214 respondents. Measuring instrument used is a standard questionnaire sheet Pittsburg Sleep Quality Index (PSQI) and the factors affecting the quality of sleep with Cronbach Alpha 0.951. Results were analyzed using univariate analysis that describes the frequency distribution and bivariate analysis using Chi-square test. The research showed there were factors that affect the quality of sleep. They were environmental factors (p value 0,018), emotional stress factors (p value 0,005) and motivational factors/coping (p value 0,019). Based on the results of the study, the researchers suggested the students to be able to maintain a good quality sleep that the factors that affect the quality of sleep does not happen. Keywords: Factors, Pittsburg Sleep Quality Index (PSQI), Quality of sleep